(untitled) (International Journal of Language, Literacy and Translation, 2025)
This study investigates the effects of Beginning-Middle-End (BME) strategy on the improvement of English writing skills among the lower proficiency language learners in a secondary school located in the state of Kedah. Utilising the BME within language classroom is seen as a valuable approach which offers assistance to lower proficient learners to progress in their English writing skills. Writing is a common issue affecting most second language learners (ESL) as these would lead the learners to lose motivation in learning writing in English. Although writing is without doubt the most challenging proficiency to be acquired, it is a vital skill to measure learners’ level of proficiency in English language. The objective of this study is to assess the effectiveness of BME strategy in improving writing skills among secondary school learners. This quasiexperimental study was conducted within a 4 month period where twenty seven samples were given one writing lesson per week involving an in-depth BME intervention. Data was collected via the pre- and post-test. The post-test scores indicate that learners have developed better writing skill with the intervention of BME strategy. The findings identified that participants improved significantly in their writing skills. Implementation of BME to improve writing skill is a worthy strategy which ought to be adopted in teaching lower proficiency English language learners.